Empire and Catastrophe Decolonization and Environmental Disaster in North Africa and Mediterranean France since 1954 - Segalla, Spencer (France Overseas: Studies in Empire and Decolonization, 2020)
"Empire and Catastrophe examines natural and anthropogenic disasters during the years of decolonization in Algeria, Morocco, and France, and explores the ways in which environmental catastrophes both shaped and were shaped by struggles over the dissolution of France's empire in North Africa. Four disasters make up the core of the book: the 1954 earthquake in Algeria's Chélif Valley, just weeks before the onset of the Algerian Revolution; a mass poisoning in Morocco in 1959 caused by toxic substances from an American military base; the 1959 Malpasset dam collapse in Fréjus, France, which devastated the Algerian immigrant community in the town but which was blamed on Algerian sabotage; and the 1960 earthquake in Agadir, Morocco, which set off a public relations war between the United States, France, and the Soviet Union, and which ignited a Moroccan national debate over modernity, identity, architecture, and urban planning. Empire and Catastrophe is the first book-length study of environmental disasters during the decolonization of the French empire. Interrogating distinctions between agent and environment and between political and environmental violence, through the lenses of state archives and through the remembered experiences and literary representations of disaster survivors, this book argues for the integration of environmental events into narratives of political and cultural decolonization. Empire and Catastrophe will be sought after by environmental historians and North Africa area studies specialists as well as historians of France and French imperialism. Written in engaging prose, the book will appeal to the broader public's interest in natural disasters, and will become required reading for undergraduates in courses on natural disasters in world history."